A novel compound heterozygous fshr variant associated with primary amenorrhea: The first case report in Vietnam - Trang, Dao Thi; Khai, Nguyen Thi Minh; Nga, Nguyen Thi; Ngoc, Nguyen Thi Minh; Trang, Nguyen Thi; Lan, Hoang Thu (Tạp chí Nghiên cứu Y học, 2026)
Primary amenorrhea is a rare condition with heterogeneous causes, including anatomic and sexual development problems, ovarian insufficiency, hypothalamus or pituitary illnesses, and other endocrine gland disorders. Genetic etiology may involve chromosomal abnormalities or gene mutations. Variants in the follicle-stimulating hormone receptor (FSHR) gene are extremely rare, with only a few cases reported worldwide. We describe a 32-year-old Vietnamese female with primary amenorrhea and repeated in vitro fertilization failure due to absent ovarian response. She exhibited a small uterus on ultrasound, and hormonal testing results of ovarian insufficiency status and a normal 46,XX karyotype. Clinical exome sequencing revealed an in trans compound heterozygous FSHR variant: c.656_659del and c.263C>T, which were classified as likely pathogenic and variant of uncertain significance with high possibility of pathogenicity, accordingly. Despite gonadotropin stimulation at a high dose, the woman failed to produce mature oocytes. This study reports the first Vietnamese case with primary amenorrhea that is related to novel FSHR variants. The findings expand the FSHR mutation spectrum and underscore the importance of genetic testing and counseling in unexplained ovarian insufficiency.